2014
DOI: 10.1016/j.neuroimage.2013.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Oral contraceptive pill use and menstrual cycle phase are associated with altered resting state functional connectivity

Abstract: At rest, brain activity can be characterized not by an absence of organized activity but instead by spatially and temporally correlated patterns of activity. In this experiment, we investigated whether and to what extent resting state functional connectivity is modulated by sex hormones in women, both across the menstrual cycle and when altered by oral contraceptive pills. Sex hormones have been shown to have important effects on task-related activity, but few studies have investigated the extent to which they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
174
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(207 citation statements)
references
References 89 publications
24
174
3
1
Order By: Relevance
“…Specifically, Petersen et al [94] found higher connectivity in the right anterior cingulate region for women tested in the menstrual phase (which they refer to as ‘early follicular’) as compared to the luteal phase, as well as higher connectivity in the left MFG in the menstrual phase as compared to women taking hormonal contraceptives. Despite of several methodological similarities between this and the current study, there were also some differences that might partly account for the conflicting findings.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Petersen et al [94] found higher connectivity in the right anterior cingulate region for women tested in the menstrual phase (which they refer to as ‘early follicular’) as compared to the luteal phase, as well as higher connectivity in the left MFG in the menstrual phase as compared to women taking hormonal contraceptives. Despite of several methodological similarities between this and the current study, there were also some differences that might partly account for the conflicting findings.…”
Section: Discussionmentioning
confidence: 99%
“…Women using hormonal contraceptives have significantly larger prefrontal cortices, pre-and postcentral gyri, parahippocampal, and fusiform gyri and temporal regions, compared to women not using contraceptives (495). Resting state functional connectivity between the left angular gyrus, middle frontal gyrus, and anterior cingulated cortex are modulated by menstrual cycle phase and oral contraceptive use (489). In particular, oral contraceptive use and the luteal phase are associated with reduced connectivity between these regions, which are associated with cognitive and affective control (489).…”
Section: Estrogens and Prefrontal Cortex-dependent Cognitionmentioning
confidence: 94%
“…Resting state functional connectivity between the left angular gyrus, middle frontal gyrus, and anterior cingulated cortex are modulated by menstrual cycle phase and oral contraceptive use (489). In particular, oral contraceptive use and the luteal phase are associated with reduced connectivity between these regions, which are associated with cognitive and affective control (489). Further, interhemispheric correlation between frontal regions is higher during ovulation and lower in the menses phase, whereas the opposite pattern in intrahemispheric connectivity is seen in occipital regions (583).…”
Section: Estrogens and Prefrontal Cortex-dependent Cognitionmentioning
confidence: 99%
“…Chen, Wu, Lua, Mikyakoshi, & Nakai, 2013; Damoiseaux et al, 2008;Filippi et al, 2013; Hu et al, 2013;Petersen, Kilpatrick, Goharzad, & Cahill, 2014;Tian, Wang, Yan, & He, 2011). As transsexuals exhibit sex-atypical anatomy in several brain regions (see paragraph "Brain morphometry"), knowing whether resting-state patterns of transsexuals resemble those of subjects with the same biological sex or rather those with the same gender identity is potentially meaningful.…”
mentioning
confidence: 99%